The Craft of Emotion in Isabel Allende's Paula - Susan Carvalho (Studies in 20th & 21st Century Literature, 2003)
Isabel Allende's narrative, from her first novel The House of the Spirits (1982) through the most recent works, has often been branded as "sentimental..."
Keywords: The House of the Spirits; sentimental; emotion; Isabel Allende